DETERMINAN ONLINE REPURCHASE INTENTION PRODUK EMAS ANTAM MELALUI WEBSITE WWW.LOGAMMULIA.COM (STUDI PADA GENERASI MILLENIAL DI BALI) - Tirtayani, I Gusti Ayu; Kustina, Ketut Tanti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
Investment in gold is a form of investment that is in great demand by investors from all walks of life, especially the millennial generation. The purpose of this study is to analyze the determinants of online repurchase intention of Antam's gold products through the website www.logammulia.com. The population in this study is infinite, so the number of samples used is 10 x 10 indicators = 100 samples. The sampling method used in this study is non-probability sampling. the study was tested using SEM-PLS analysis using the Warp-PLS version 3.0 program. Perceived Website Quality (pwq) and E-Trust (etrust) are the two main factors influencing consumer decisions in repurchasing Antam's gold products online. Perceived Website Quality (pwq) has a significant influence on E-Trust (etrust) and Online Repurchase Intention (ori). E-Trust (etrust) also has a significant influence on Online Repurchase Intention (ori).